Diurnal rhythm of cortisol during late pregnancy: Associations with maternal psychological well-being and fetal growth - Kivlighan, Katie T. (2008)
Maternal psychological functioning during pregnancy affects both maternal and fetal well-being. The hypothalamic-pituitary-adrenal (HPA) axis provides one mechanism through which maternal psychosocial factors may be transduced to the fetus. However, few studies have examined maternal psychological factors or birth outcomes in relation to the diurnal pattern of cortisol across the day. The current study examined maternal psychological well-being, parity status, and birth weight in relation to the maternal cortisol diurnal rhythm in a group of 98 low-risk pregnant women (51 primiparae). At 36 weeks gestation, participants completed both pregnancy-specific and general self-report measures of psychological functioning and provided saliva samples at 800, 1200, and 1600h on 2 consecutive working days for the assay of cortisol. The expected diurnal decline in salivary cortisol was observed. Higher trait anxiety was associated with a flatter afternoon decline for all mothers. For primiparae, steeper morning cortisol declines were associated with lower infant birth weight. The findings suggest that regulation of the HPA axis may differ by parity status with downstream implications for fetal growth and development.